2006
DOI: 10.1007/s11224-006-9050-0
|View full text |Cite
|
Sign up to set email alerts
|

Experimental, theoretical and biological activity study on 1-(4,5-dihydro-3-arylpyrazol-1-yl)-2-(1H-1,2,4-triazol-1-yl)-ethanone

Abstract: Four compounds have been synthesized and characterized by 1 H NMR spectroscopy and elemental analyses, among which 1-(4,5-dihydro-3-phenyl-pyrazol-1-yl)-2-(1H-1,2,4-triazol-1-yl)ethanone 3a was further confirmed by X-ray crystallographic analysis. The biological activities of these compounds were tested, with the result that they displayed moderate fungicidal activities. In addition, a MO calculations using density functional theory (DFT) at B3LYP/6-31G * level have also been carried out, and the structure-act… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…As to the theoretical level, B3LYP method and valence double or triple zeta basis set is currently most popular (e.g. articles published in Structural Chemistry in the years 2005 and 2006 [13][14][15][16][17][18][19][20][21][22][23]). Calculations utilizing only HF theory, which neglects dynamic electronic correlation, were also often reported [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…As to the theoretical level, B3LYP method and valence double or triple zeta basis set is currently most popular (e.g. articles published in Structural Chemistry in the years 2005 and 2006 [13][14][15][16][17][18][19][20][21][22][23]). Calculations utilizing only HF theory, which neglects dynamic electronic correlation, were also often reported [24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…As continuation of research for better herbicidal and fungicidal activities study, Xu et al [134] reported in the next paper report the syntheses and characterization of four new compounds containing 1H-1,2,4-triazole and 4,5-dihydro-1H-pyrazole frameworks. Biological tests of synthesized compounds showed their moderate fungicidal activities.…”
Section: Issuementioning
confidence: 92%
“…Propiconazole and difenoconazole are two important representatives of this class, especially the latter, which has been used as the most efficient triazole fungicide in the control of some common plant diseases [5,6]. Consequently, spurred by the need for new antifungal agents and the fact that many new effective fungicides possess heterocyclic rings in their structure, such as 1,2, 4-triazole ring, over the last few years we have synthesized some novel 1,2,4-triazole derivatives [7] and tested them for antifungal activity against Gibberella zeae, Alternaria solani, Phoma asparagi, Physalospora pircola, and Cercospora arachidicola. The results of preliminary biological tests showed that all of these compounds possess certain antifungal activities.…”
Section: Introductionmentioning
confidence: 99%